MENINGKATAN PRESTASI BERMAIN BOLA VOLI DENGAN BANTUAN BOLA GANTUNG PADA SISWA KELAS IV - Weli, Weli; Haetami, Mimi; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractProblems in research this is how the influence of a method of the ball hanging on increased achievement play volley ball students. The purpose of this research is to know how big increase achievement play volley ball students in serve and passing. Methods used in research ptk with the sample collection students. The study is done 2 cycles made during 3 hours three time 35 minutes. The result students cycle 1 45% to 55% work completed in serve and passing while cycle 2 originally 55% to 75%. So that it can be concluded that with use some halp volley ball to their students fourth grade MIS Mathlaâ€™ul Anwar.Â Keywords: Achievement play voly, the ball hanging.